The Effect of Sales Growth, Business Risk, and Asset Structure on Capital Structure: Evidence from Metal and Related Subsector Companies Listed on the Indonesia Stock Exchange During the 2019–2022 Period - Bambang Wahyudi Wicaksono; Edi Wahyu Wibowo; Enjelina Sari (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to determine the simultaneous and partial effects of sales growth, business risk, and asset structure on the capital structure of companies in the metal and allied sub-sectors listed on the Indonesia Stock Exchange from 2019 to 2022. An associative research method was employed, utilizing a sample of 15 companies from the metal and allied sub-sectors selected via purposive sampling. Data analysis techniques included descriptive statistics, panel data regression modeling, multiple linear regression, the coefficient of determination, F-tests and t-tests, and classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation). The F-test results indicate that sales growth, business risk, and asset structure simultaneously have a significant effect on capital structure. The t-test results show that sales growth has a partial effect on capital structure, whereas business risk and asset structure do not have a partial effect on capital structure. Keywords: Sales Growth, Business Risk, Asset Structure, Capital Structure